Promoting sexual health equity in the United States: implications from exploratory research with African-American adults - Friedman, Allison L. (Health Educ Res, 2014)
In an effort to inform communication efforts to promote sexual health equity in the United States, the Centers for Disease Control and Prevention sought to explore African-Americans’ perceptions of the sexually transmitted disease (STD) problem in their communities, reactions to racially comparative STD data and opinions about dissemination of such information. Semi-structured triads and individual interviews were conducted with African-American adults (N = 158) in the Southeastern and Midwestern United States. Most participants believed that STDs are a problem in their communities but were unaware of the extent to which STDs disproportionately affect African Americans. Once informed about racial differences in STD rates, participants commonly reacted with shock, fear and despair; a minority raised questions about the information’s source and credibility. Most felt it was critical to get the information out to African-American communities as a ‘wake-up call’ to motivate change, though some raised concerns about its dissemination. Findings suggest that information about racial differences in STD rates must be strategically crafted and delivered through targeted channels to be acceptable to African Americans. So as not to further harm communities burdened by other social/health inequities, alternative (strength-based) approaches should be considered for motivating positive change.